Simulasi Pemodelan Dampak Pengobatan yang Tidak Lengkap pada Penyebaran Tuberkulosis - Muna Afdi Muniroh (Department of Mathematics, Hasanuddin University, 2025)
Among the most common diseases globally is tuberculosis (TB). The spread dynamics of TB are formulated in the form of a mathematical model with five subpopulation densities, namely, susceptible individuals, latent individuals, TB active individuals, treated individuals, and recovered individuals. The existence of an equilibrium point is contingent upon the value of the basic reproduction number Ro. Ro is a key metric for understanding the potential for disease transmission and is obtained from the next generation matrix. Stability analysis for TB models is investigated by determining the criteria for the local stability of equilibrium points. After that, a sensitivity analysis is conducted to identify TB model parameters that most affect Ro value. The solution behavior of the TB model is shown by graphs generated numerically with the Runge-Kutta fourth-order method and Matlab software